Self-esteem of adolescent victims of bullying - Nadia Sintia Wardany; Wawan Rismawan; Ilham Jihad Akbar (Jurnal EduHealth, 2024)
According to ICRW (2015), bullying that occurs in Indonesian education areas (84%) is higher than countries in Asia. However, not many people understand the long-term impact of bullying behavior, namely mental disorders and decreased self-esteem. This study aims to describe the level of self-esteem in adolescent victims of bullying in grade 1 of MTs Mu'min Ma'shum. This study uses a quantitative descriptive method to adolescent victims of bullying to describe the level of self-esteem. The results of the study, men tend to be victims of bullying (76.9%). Of the 26 students, 21 students (80.8%) had normal self-esteem and 5 students (19.2%) had low self-esteem. All students experienced verbal bullying, with an average age of 14 years. The most common sex is male with an average age of 14 years. The most common type of bullying is verbal bullying and the highest level of self-esteem is normal self-esteem. For future research it is hoped to examine the triggering factors of bullying and the relationship between characteristics and self-esteem levels.